ASUPAN SENG YANG RENDAH SEBAGAI FAKTOR RISIKO KEPARAHAN PNEUMONIA PADA ANAK USIA 12-59 BULAN - Nasution, Meiry; Hakimi, Mohammad; Hartini, Ninuk Sri (PERSATUAN AHLI GIZI INDONESIA, 2017)
Period prevalence of infant pneumonia in Indonesia is 18.5 per mile. The high mortality rate due to pneumonia of 62 percent was found in 10 countries and 5 countries was located in Asia. Zinc is one of micronutrients which is reported to prevent pneumonia as an acute phase response to infection and help to boost the body immune response. The objective of the study was to determine the impact of zinc intake as risk factor of severe pneumonia in children. A case control study was conducted among children aged 12–59 months in 2 hospitals and 6 health centres, Yogyakarta city. Thirty four children were categorized as having severe pneumonia (cases) and 102 children were categorized as having pneumonia (control). All sample’s mothers completed a semi-quantitative food frequency questionnaire during March-April 2014. Data analysis was performed using Mantel-Haenszel test and conditional logistic regression, α = 0,05. Results of the study showed that there were 41.2 percent cases and 56.9 percent control were exclusively breast-fed. The proportion of cases who had inadequate zink intake was higher than control group. There was no difference between inadequate zinc intake and the severe pneumonia (OR 1,08 and 95% CI 0,5-2,3). There was a statistically significant correlation between low-zinc intake and severe pneumonia if second disease exist (OR 3,8 and 95% CI 1,4 -10,8). As an conclusion, Inadequate zinc intake affected severe pneumonia when the secondary diseases exist in children with pneumonia. ABSTRAK Period prevalence pneumonia balita di Indonesia adalah 18,5 per mil. Angka kematian yang tinggi akibat pneumonia sebesar 62 persen terdapat di 10 negara dan 5 negara di antaranya merupakan negara di Asia. Defisiensi seng menyebabkan penurunan kekebalan sel sehingga meningkatkan kerentanan terhadap penyakit pneumonia. Tujuan penelitian ini menganalisis asupan seng yang kurang sebagai faktor risiko keparahan pneumonia pada anak. Desain penelitian case control pada 136 anak usia 12-59 bulan yang diperoleh dari 2 RS dan 6 puskesmas di Kotamadya Yogyakarta. Sampel terdiri dari 34 anak menderita pneumoni berat (kasus) dan 102 anak menderita pneumonia sebagai kontrol. Ibu sampel melengkapi data asupan seng melalui frekuensi makan semi-kuantitatif pada bulan Maret-April 2014. Sejumlah 45 makanan dicantumkan pada kuesioner frekuensi makan. Analisis data dilakukan dengan uji Mantel-Haenszel dan regresi logistik bersyarat dengan α =0,05. Hasil penelitian menunjukkan bahwa sejumlah 41,2 persen kelompok kasus dan 56,9 persen kontrol mendapat air susu ibu (ASI) eksklusif. Proporsi kasus yang asupan sengnya kurang ternyata lebih tinggi dari kelompok kontrol. Tidak ada perbedaan antara asupan seng dan keparahan pneumonia (OR 1,08 dan 95% CI 0,5-2,3). Ada korelasi yang signifikan antara asupan seng yang kurang dan keparahan pneumonia jika disertai penyakit penyerta (OR 3,8 dan 95% CI 1,4 -10,8). Kurangnya asupan seng berpengaruh terhadap terjadinya keparahan pneumonia jika disertai adanya penyakit penyerta pada anak-anak penderita pneumonia usia 12-59 bulan. Kata kunci: asupan seng, pneumonia, faktor risiko, anak usia 12-59 bulan